2016
DOI: 10.1088/0031-9155/61/4/1546
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MLC tracking performance during hypofractionated prostate radiotherapy using real-time dose reconstruction

Abstract: By adapting to the actual patient anatomy during treatment, tracked multi-leaf collimator (MLC) treatment deliveries offer an opportunity for margin reduction and healthy tissue sparing. This is assumed to be especially relevant for hypofractionated protocols in which intrafractional motion does not easily average out. In order to confidently deliver tracked treatments with potentially reduced margins, it is necessary to monitor not only the patient anatomy but also the actually delivered dose during irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 33 publications
0
65
0
Order By: Relevance
“…Therefore, at least 4D dose re‐calculations are desired after each treatment fraction. Examples for 4D dose reconstructions have already been reported for scanned carbon beam therapy and photon therapy using dynamic multi‐leaf collimator tracking . This study has shown that the model is able to predict CT images corresponding to respiratory states described by two parameters (phase and amplitude) combined with information on the inter‐fraction anatomical variations with respect to the planning CT.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, at least 4D dose re‐calculations are desired after each treatment fraction. Examples for 4D dose reconstructions have already been reported for scanned carbon beam therapy and photon therapy using dynamic multi‐leaf collimator tracking . This study has shown that the model is able to predict CT images corresponding to respiratory states described by two parameters (phase and amplitude) combined with information on the inter‐fraction anatomical variations with respect to the planning CT.…”
Section: Discussionmentioning
confidence: 80%
“…Figure describes the actual online dose reconstruction step‐by‐step, in line with our previous work in Fast et al . DynaTrack sends actual MLC apertures and target positions to DynaPlan immediately after they are available.…”
Section: Methodsmentioning
confidence: 89%
“…Previously, DynaTrack was used for either conformal deliveries, S&S IMRT, or conformal VMAT . In this study, standard VMAT was supported for the first time.…”
Section: Methodsmentioning
confidence: 99%
“…Several methods have been proposed to compute the delivered dose based on offline dose reconstruction 15 , 16 , 17 , 18 . Recently, we have presented an online dose reconstruction solution for assessment of prostate SBRT, 19 which calculates and accumulates dose in real‐time based on dose‐influence data, while accounting for the machine/target motion interplay. Dose‐influence data describe the influence of the fluence distribution on the patient dose.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, accumulating the dose onto a reference phase requires deformable image registration (DIR) and a real‐time dose mapping algorithm. We add to our previously presented online dose reconstruction platform 19 by providing implementations for each of these challenges.…”
Section: Introductionmentioning
confidence: 99%